MEMBANGUN KONEKSI DAN KOLABORASI GENERASI Z DAN ALPHA: PRAKTIK MANAJEMEN KELAS - Iwan Perdana; Yuliana Nurhayati; Maulidha Maulidha (Bajang Institute, 2025)
This community service activity aims to enhance the understanding and skills of teachers at SMK Islam Sabilal Muhtadin Banjarmasin in managing Generation Z and Alpha students through lecture-based instruction and interactive discussions. Participants comprised 23 teachers who attended a lecture on generational characteristics, pedagogical challenges, and principles of classroom management grounded in connection and collaboration, followed by interactive discussions to explore classroom experiences and how teachers address them. The evaluation results showed an increase in participants' understanding of identifying the learning needs of the new generation and in designing collaborative and valuable learning strategies. The combination of lecture methods and interactive discussions is effective in building awareness, critical reflection, and the preparation of contextual action plans